Current Distribution of Two Species of Tylos (Isopoda: Oniscidea) in the Central Mediterranean and the Influence of Beach Sand Grain-Size Parameters. Issue 1 (1st January 2014) - Montesanto, Giuseppe; Deidun, Alan; Sciberras, Arnold; Sciberras, Jeffrey; Lombardo, Bianca Maria
Abstract: The psammophilic genus Tylos Audouin, 1826 is represented within the Mediterranean basin as two species: T. ponticus Grebnicki, 1874, and T. europaeus Arcangeli, 1938, according to Taiti and Ferrara (1996) . It is impossible to define precisely the current distribution of the two species, mainly because, in literature, both taxa have been described as subspecies of T. latreillii or even, in some cases, as T. latreillii sensu lato . The current study surveyed populations of Tylos spp. on sandy beaches along the coastline of Sicily, circum-Sicilian islands and the Maltese archipelago. The aims of this study are to fully and correctly identify all the sampled populations, pursuant to characterizing the current distribution of the two species, which occupy similar ecological niches, and to investigate any possible granulometric preferences by the two species. Data acquisition proceeded along three tiers: in situ sampling, manually and through the deployment of pitfall trap constellations, literature review and by analyzing preserved specimens of Tylos held within the 'Caruso' collection (University of Catania, Catania, Italy). Generally, T. europaeus showed a preference for fine sand, whilst T. ponticus showed a preference for fine-medium sand, although, statistically, differences in the distribution of the two species could not be explained in terms of median grain size. The two species were never recorded on the same beach. The degree of inter-specific morphological differentiation was also evaluated through a detailed morphological study of sampled Tylos spp.